KAJIAN PROSES PRODUKSI MINYAK KELAPA DENGAN MENGGUNAKAN ALAT DAN MESIN PENGOLAHAN KELAPA SKALA INDUSTRI KECIL - Defly I. C. Hansang; Dedie Tooy; Daniel P.M. Ludong (Universitas Sam Ratulangi, 2022)
ABSTRACT Coconut oil is one of the potential coconut processing products to increase the added value for farmers in North Sulawesi. Actually, quite a lot of coconut oil processing has been done by North Sulawesi farmers, but the manufacturing process still uses a lot of traditional equipment. So the processing is less efficient and takes a long time. In an effort to increase coconut oil productivity, the government has provided assistance with small industrial scale coconut oil processing equipment to several farmer groups in the community and socialized how to process coconut oil from input to output. The purpose of this research is to examine the coconut oil production process using small industrial scale coconut processing tools and machines. This research was conducted with an experimental method in which several equipments were tested . The materials used were hybrid coconut and coconut in mapanget aged 11-12 months and also KOH and bentonite, as many as 750 coconuts each. Coconut processing on the existing equipment system carried out in this study is, peeling, washing, cleaning, draining, squeezing, separating and left for 24 hours. After 24 hours, the resulting coconut cream is cooked using a frying pan with the same stove for cooking the coconut cream then heated for 1/2 hour at a controlled temperature. The results of cooking are continued using a mixer, vacuum, filtering, packaging. The performance of the tool is influenced by the existing power transmission engine, and the skill of the operator in each stage of work is very important. It is recommended for maximum use of the tool, given special training to the operator.